Bubbles in the Finnish and US equities markets - Katja Taipalus (Bank of Finland, 2006)
Tests for unit roots in log dividend yields, which are consistent with `rational bubbles' in stock prices, are conducted for the S&P500 and Finnish stock market indexes.In addition to the traditional unit root tests, we split the data into 10-year segments and use frequency domain analysis to test for the presence of unit roots in the dividend yield data.The results strongly suggest the existence of bubbles in both the US and Finnish markets.Finally we develop a novel dividend yield-based method to track periods when stock prices divert their fundamental levels. This indicator produces promising results, as it seems to have some forecasting ability concerning booms and busts in the stock markets.
URN:NBN:fi:bof-201408071677
Keywords: P50; 330; equity price; bubble; rolling ADF; Kapitalanlage; Aktienmarkt; Spekulationsblase; Dividende; Vergleich; USA; Finnland